2002
DOI: 10.1164/rccm.2109013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Augmentation Therapy on Bronchial Inflammation in α1-Antitrypsin Deficiency

Abstract: alpha1-Antitrypsin (AAT) deficiency predisposes to bronchitis and emphysema associated with neutrophilic airway inflammation. The efficacy of augmentation therapy has not been proven clinically or by demonstrating an effect on airway inflammation. We treated 12 patients with four infusions of Prolastin (60 mg/kg) at weekly intervals and monitored both the serum and secretion concentrations of AAT as well as markers of neutrophilic inflammation, including myeloperoxidase, elastase, and the neutrophil chemoattra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 25 publications
3
91
0
2
Order By: Relevance
“…In this context, biochemical markers changing quickly following a therapeutic intervention, such as the decrease in sputum levels of leukotriene B 4 , interleukin-8 or neutrophil elastase after a few weeks of supplementation therapy with i.v. a 1 -AT [60], although correlated with the disease's inflammatory processes, cannot be considered a replacement for true clinical outcomes.…”
Section: Conclusion: Is Evaluation Of Desmosine and Isodesmosine Wormentioning
confidence: 99%
“…In this context, biochemical markers changing quickly following a therapeutic intervention, such as the decrease in sputum levels of leukotriene B 4 , interleukin-8 or neutrophil elastase after a few weeks of supplementation therapy with i.v. a 1 -AT [60], although correlated with the disease's inflammatory processes, cannot be considered a replacement for true clinical outcomes.…”
Section: Conclusion: Is Evaluation Of Desmosine and Isodesmosine Wormentioning
confidence: 99%
“…However, despite the observed clinical effects of AAT, further proof of the mechanism of action of augmentation therapy is required (42). Moreover, although AAT augmentation therapy has been shown to affect sputum levels of LTB 4 (43), the potential of AAT as a BLT1 antagonist is a novel concept. Consequently, this study has identified a pathogenic mechanism associated with AATD and illustrates the anti-inflammatory efficiency of AAT augmentation therapy by modulation of the LTB 4 / BLT1 pathway in human neutrophils.…”
mentioning
confidence: 99%
“…Consistent with these biological observations, a variety of inflammatory diseases have been associated with the over-production of leukotriene B 4 . Some of these diseases are sepsis [47][48][49][50], shock [51,52], cystic fibrosis [53][54][55][56][57], coronary artery disease [58][59][60] connective tissue disease [19,[61][62][63][64][65], and COPD [66][67][68]. The biosynthesis of leukotriene B 4 is initiated by the conversion of arachidonic acid to leukotriene A 4 , which requires sequential actions by 5-lipoxygenase and 5-lipoxygenase activating protein.…”
Section: The Dual Catalytic Activities Of the Leukotriene A 4 Hydrolamentioning
confidence: 99%